-x+23=3(4x-4)+9

Simple and best practice solution for -x+23=3(4x-4)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+23=3(4x-4)+9 equation:


Simplifying
-1x + 23 = 3(4x + -4) + 9

Reorder the terms:
23 + -1x = 3(4x + -4) + 9

Reorder the terms:
23 + -1x = 3(-4 + 4x) + 9
23 + -1x = (-4 * 3 + 4x * 3) + 9
23 + -1x = (-12 + 12x) + 9

Reorder the terms:
23 + -1x = -12 + 9 + 12x

Combine like terms: -12 + 9 = -3
23 + -1x = -3 + 12x

Solving
23 + -1x = -3 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
23 + -1x + -12x = -3 + 12x + -12x

Combine like terms: -1x + -12x = -13x
23 + -13x = -3 + 12x + -12x

Combine like terms: 12x + -12x = 0
23 + -13x = -3 + 0
23 + -13x = -3

Add '-23' to each side of the equation.
23 + -23 + -13x = -3 + -23

Combine like terms: 23 + -23 = 0
0 + -13x = -3 + -23
-13x = -3 + -23

Combine like terms: -3 + -23 = -26
-13x = -26

Divide each side by '-13'.
x = 2

Simplifying
x = 2

See similar equations:

| 4(x-3)=-44 | | 4-(3x+2)=2(x+6) | | x+27=3(3x+1) | | 7p+5=12 | | 5x+7=3(2x+2) | | 0=4x*x+2t-4 | | 8x+13=45 | | 4(3x+2)+5=-2x+27 | | -3(2n+1)+7=5 | | 4(3x+1)+10=26 | | 6a-10a-3(2a)=50-5(8) | | 4(x+4)=x+37 | | 4(x+5)=5x+23 | | 4xm+5x=10 | | S^2-9x+18=0 | | 2.252*30-29.578*30+5240.216=0 | | 5x+17=9x-8 | | 10x+6(2x+4)=32 | | 360=3x+78+(2x-12) | | 518x=70 | | X=-3x+5 | | 518x=-70 | | 6x^2+5-99=0 | | 5x^2+25x=-20 | | 212x-5000-x^2=0 | | 37(14x)+28(21x)=[72-72]+[-166+96] | | 7(a-2)=2(2a-1) | | -16t^2-4t+930=0 | | 84.487=-.012x^2+1.242x+64.447 | | -14x^2+1400x-29400=0 | | 5a+-11=3a+-3 | | 4x^2-29x+4x=-2x+5 |

Equations solver categories